Competencies of an Arabic language teacher for non-native speakers - Issa, Alaa Faisal; Alabed, Abdulbaki Hussein Alzayel (Journal of Educational and Psychological Sciences, 2022)
The current research aims to complete a theoretical study related to the importance of preparing Arabic language teachers for speakers of other languages according to the approach of the basic and subsidiary competencies that a successful teacher should have. The research followed the descriptive analytical method to reach the results to be searched. The research reached a number of results, including: 1- The lack of research and studies concerned with preparing teachers according to the competency approach, and their scarcity in the field of teaching Arabic to speakers of other languages. 2- The importance of cultural, professional, specialized, performing, personal and social competencies, and the sub-competencies they include. 3- The study showed the need of Arabic language teachers for speakers of other languages for continuous preparation before and during the education process in order to provide them with the necessary competencies. 4- The teacher’s accumulated experiences, good preparation, and effective skill abilities lead them to make the teaching-learning process successful. In light of the findings of the research, it recommended a number of recommendations: 1. The necessity for the Arabic language teaching institutions and institutes in the Arab world to pay attention to preparing Arabic language teachers for speakers of other languages according to the competency approach. 2. Teacher preparation institutions should take into consideration the importance of the competencies and qualities that a teacher of Arabic for speakers of other languages must possess in order to be successful.